Transcriptomic Analysis of Seed Germination Under Salt Stress in Two Desert Sister Species (Populus euphratica and P. pruinosa) - Zhang, Caihua; Luo, Wenchun; Li, Yanda; Zhang, Xu; Bai, Xiaotao; Niu, Zhimin; Zhang, Xiao; Li, Zhijun; Wan, Dongshi (Frontiers in Genetics, 2019)
As a major abiotic stress, soil salinity limits seed germination and plant growth, development and production. Seed germination is highly related not only to the seedlings survival rate but also subsequent vegetative growth. Populus euphratica and P. pruinosa are closely related species that show a distinguished adaptability to salinity stress. In this study, we performed an integrative transcriptome analyses of three seed germination phases from P. euphratica and P. pruinosa under salt stress. A two-dimensional data set of this study provides a comprehensive view of the dynamic biochemical processes that underpin seed germination and salt tolerance. Our analysis identified 12831 differentially expressed genes (DEGs) for seed germination processes and 8071 DEGs for salt tolerance in the two species. Furthermore, we identified the expression profiles and main pathways in each growth phase. For seed germination, a large number of DEGs, including those involved in energy production and hormonal regulation pathways, were transiently and specifically induced in the late phase. In the comparison of salt tolerance between the two species, the flavonoid and brassinosteroid pathways were significantly enriched. More specifically, in the flavonoid pathway, FLS and F3′5′H exhibited significant differential expression. In the brassinosteroid pathway, the expression levels of DWF4, BR6OX2 and ROT3 were notably higher in P. pruinosa than in P. euphratica. Our results describe transcript dynamics and highlight secondary metabolite pathways involved in the response to salt stress during the seed germination of two desert poplars.